Heme Oxygenase-1 and Brain Oxysterols Metabolism Are Linked to Egr-1 Expression in Aged Mice Cortex, but Not in Hippocampus - Rosa, Paolo; Zerbinati, Chiara; Crestini, Alessio; Canudas, Anna-Maria; Ragona, Giuseppe; Confaloni, Annamaria; Iuliano, Luigi; Calogero, Antonella (Frontiers in Aging Neuroscience, 2018)
Throughout life, stress stimuli act upon the brain leading to morphological and functional changes in advanced age, when it is likely to develop neurodegenerative disorders. There is an increasing need to unveil the molecular mechanisms underlying aging, in a world where populations are getting older. Egr-1 (early growth response 1), a transcriptional factor involved in cell survival, proliferation and differentiation – with a role also in memory, cognition and synaptic plasticity, can be implicated in the molecular mechanism of the aging process. Moreover, Heme Oxygenase-1a (HO), a 32 kDa heat-shock protein that converts heme to iron, carbon monoxide and biliverdin, is a key enzyme with neuroprotective properties. Several in vitro and in vivo studies reported that HO-1 could regulate the metabolism of oxysterols, oxidation products of cholesterol that include markers of oxidative stress. Recently, a link between Egr-1 and HO-1 has been demonstrated in mouse lung cells exposed to cigarette smoke. In view of these data, we wanted to investigate whether Egr-1 can be implicated also in the oxysterol metabolism during brain aging. Our results show that Egr-1 expression is differently expressed in the cortex and hippocampus of old mice, as well as the oxysterol profile between these two brain areas. In particular, we show that the cortex experiences in an age-dependent fashion increasing levels of the Egr-1 protein, and that these correlate with the level of HO-1 expression and oxysterol abundance. Such a situation was not observed in the hippocampus. These results are further strenghtened by our observations made with Egr-1 KO mice, confirming our hypothesis concerning the influence of Egr-1 on oxysterol production and accumulation via regulation of the expression of HO-1 in the cortex, but not the hippocampus, of old mice. It is important to notice that most of the oxysterols involved in this process are those usually stimulated by oxidative stress, which would then represent the triggering factor for this mechanism.